Changes in plantar pressure, force and contact area when carrying incremental loads among adults with and without low back pain - Deepashini Harithasan,; Devinder Kaur Ajit Singh,; Baharudin Omar, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Plantar pressure, force and contact area information may provideinsights regarding stresses imparted to the foot when performing functional tasks. There is limited information regarding plantar pressure, force and contact area when carrying incremental loads (no load, 5 kg, 7.5 kg and 10 kg) using one hand between adults with and without low back pain (LBP). The aim of our study was to investigate the changes in the plantar pressure, force and contact area when carrying incremental loads (no load, 5 kg, 7.5 kg and 10 kg) using one hand between adults with and without low back pain (LBP). A total of 20 adults with non-specific LBP and 20 matched individuals without LBP were recruited according to the predefined recruitment criteria. Plantar pressure (PP), maximum force (MF) and contact area (CA were measured in standing position and during walking while carrying incremental loads (no load, 5 kg, 7.5 kg and 10 kg) using their right hand on a Matscan pressure assessment system. A two-way mixed analysis of variance (group× load) was conducted to analyse the data. No significant main effectof group was demonstrated on both the right and left foot during standing (PP: p = 0.74, p = 0.32; MF: p = 0.17, p = 0.67; CA: p = 0.25, p = 0.24) and walking (PP: p = 0.61, p = 0.48; MF: p = 0.19, p = 0.06; CA: p = 0.16, p = 0.26. Similarly, there was no interaction effect between the loads and groups on the PP (p = 0.89, p = 0.47), MF (p = 0.76, p = 0.83) and CA (p = 0.88, p = 0.20) on theright and left foot, respectively during standing. However, a significant interaction effect (p < 0.05), between the loads and groups was demonstrated on the PP, MF and CA on the left foot during walking. The results of our study suggest that stresses imparted to the foot alters during dynamic postures and this may be a compensatory mechanism. Plantar pressure, force and contact area were similar in adults both with and without LBP when standing and walking. Further biomechanical information that includes both kinematic and kinetic data in lumbopelvic and lower limbs in relation to the foot may be required to justify for prevention and management strategies among adults with LBP.